Pengembangan Media Science App Berbantuan Smart Apps Creator untuk Mendukung Atensi Siswa pada Pembelajaran IPAS di Sekolah Dasar - Dwi Lailatul Khikmah; Mochammad Miftachul Huda; Ahmad Ipmawan Kharisma (Mataram University, 2026)
The use of technology in the learning process at elementary schools still faces several issues, such as the suboptimal use of digital media, limited variety of technology-based learning media, and the continued dominance of conventional teaching methods. This study aims to develop and validate the Science App learning media assisted by a smart apps creator in fostering student attention in science learning. The method used is Research and Development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages, but is limited to the development stage. Research instruments include validation sheets from material experts, media experts, and language experts. Validation results carried out by two experts showed that the media received an average score of 3.91 (material expert), an average score of 3.79 (media expert), and an average score of 3.72 (language expert). The assessment covers several aspects, namely the suitability of the material, the ease of using the media, and the clarity of the language used. The results show that the developed media has met the criteria of being very valid and feasible to use in the learning process.